SHEAR BOND STRENGTH OF CERAMIC BRACKETS BONDED TO ZIRKONIUM SURFACES AFTER DIFFERENT SURFACE PREPERATION TECHNIQUES: AN IN VITRO STUDY - Emine Karslı; Süleyman Evren Öztaş (Sabiad)
Objective: There are few studies examining the shear bond strength (SBS) of ceramic brackets (which are frequently chosen to meet aesthetic expectations), on monolithic zirconium surfaces. The aim of this study is to measure the SBS of ceramic brackets adhered to the zirconium surfaces, to which different surface roughening methods have been applied and to evaluate the rupture areas with ARI scoring. Materials and method: 40 zirconium blocks were divided into 4 equal groups and surface roughening processes performed with hydrofluoric acid (HF), sandblasting with aluminum-oxide (Al2 O3 ), Er-YAG and Nd-YAG laser. All ceramic brackets were adhered to the surfaces. The SBS values of the brackets to surfaces were recorded in MPa with a universal test machine. For ARI scoring, the surfaces were examined under x20 magnification with optical microscope. Results: the mean SBS values were 4.599±1.989, 6.879±2.037, 7.429±1.468, 5.665±2.308 MPa respectively, with the lowest being the HF group and the highest being the Er-YAG group. It was observed that the measured value in the Er-YAG group was statistically higher than the HF group. When Adhesive Remnant Index (ARI) scores were examined, it was observed that in 40% of the samples in the Er-YAG group, all residual composite remained on the zirconium. Conclusion: the SBS of the HF method, which is frequently used in orthodontic clinics, to zirconium was found insufficient. It has been shown that surface roughening of zirconium with Er-YAG laser provides more SBS with ceramic brackets.